A right to gratitude - Szawarski, Zbigniew (Acta Bioethica, 2005)
Few matters in medical ethics give rise to such passionate disputes and discussions as the issues of doctors’ acceptances of diverse kinds of gifts, services or favours from grateful patients or pharmaceutical companies interested in acquiring a physicians endorsement. Gratitude is a fundamental moral value. Modern philosophy proposes three different, rival models of gratitude. Appropriate social rules determine what, when and under what conditions counts as a reciprocation of a gift. The moral sphere between doctor and patient is incredibly complex: there appear to be four types of possible attitudes that a patient can adopt towards a physician. The art of giving is as complex as the art of receiving.